HIV-Specific CD8 T Cells Producing CCL-4 Are Associated With Worse Immune Reconstitution During Chronic Infection. (1st July 2017) - Casetti, Rita; Pinnetti, Carmela; Sacchi, Alessandra; De Simone, Gabriele; Bordoni, Veronica; Cimini, Eleonora; Tumino, Nicola; Besi, Francesca; Viola, Domenico; Turchi, Federica; Mazzotta, Valentina; Antinori, Andrea; et al.
Abstract : Background: Immunological nonresponse represents the Achilles heel in the combination antiretroviral therapy (cART) effectiveness, and increases risk of clinical events and death. CD8 T cells play a crucial role in controlling HIV replication, and polyfunctional HIV-specific CD8 T cells have been associated with nonprogressive HIV infection. However, the possible role of polyfunctional CD8 T cells in predicting posttreatment immune reconstitution has not yet been explored. The aim of this study was to identify functional markers predictive of immunological response to cART in chronic HIV-infected patients. Methods: A cohort of chronic HIV-infected individuals naive to cART were enrolled in the ALPHA study. CD4/CD8 T-cell subsets, their differentiation/activation, as well as susceptibility to apoptosis were analyzed before and after 12 months of cART. Moreover, CD8 T cells polyfunctional response after HIV antigenic stimulation was also assessed. Results: Results showed a significant correlation between worse CD4 T-cell restoration and low frequency of naive CD4 T cells, high frequency of effector memory CD4 T cells, and high susceptibility to apoptosis of CD4 T cells all before cART. Moreover, CD8 functional subsets expressing total C-C motif chemokine ligand 4 (CCL-4) or in combination with CD107a and interferon gamma (IFNγ) were negatively associated with immune reconstitution. Conclusions: In conclusion, our study shows that a more differentiated phenotype of CD4 T cells and CCL-4–producing CD8 T cells could represent valuable predictors of worse immune reconstitution. These parameters may be used as tools for identifying patients at risk of immunological failure during cART and eventually represent the basis for innovative therapeutic strategies.